Schistosomiasis at the Crossroad to Elimination: Review of Eclipsed Research with Emphasis on the Post-Transmission Agenda - Giboda, Michal; Bergquist, Robert; Utzinger, Jürg (Tropical medicine and infectious disease, 2022)
While chronic schistosomiasis is pathologically well defined, the acute form of the disease is less well understood. It is generally agreed that early lesions, such as lung nodules and bladder polyps, are reversible, which impedes identification of the time elapsed since exposure. The intermediate stage between the acute and the chronic forms of schistosomiasis requires further investigation, as does the clinical stage due to lesions remaining after treatment. With current schistosomiasis control efforts gradually progressing to elimination, there is a need to focus on post-transmission schistosomiasis, which not only refers to remaining lesions from previous infections, but also accounts for the potential presence of surviving worms after treatment. This issue is particularly salient for migrants from endemic to non-endemic countries and should be kept in mind for returning expatriates from schistosomiasis-endemic countries. Negative stool examination or urine filtration are generally taken as indicative of cure since rectoscopy for Schistosoma mansoni infection, or cystoscopy for S. haematobium infection, are rarely performed. However, pathology of affected organs may persist indefinitely, while potentially remaining live worms could produce additional pathology. Hence, post-transmission schistosomiasis can prevail for years after elimination of the disease, and thus, warrant further attention.